Pengaruh Sudu Contra Rotating Small Hydro Turbine Dengan Variasi Sudut Blade Pada Eksperimen Prototype Turbin Air - Moh Arif Batutah; Abdul Kowi; Muhammad Tohari (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2021)
The availability of non-renewable energy has recently been running low, which has an impact on electrical energy. One of the efforts to utilize renewable energy is by utilizing the kinetic energy of water. Water energy can be transferred into other forms of energy such as mechanical or electrical using a water turbine. The Contra Rotating type turbine is suitable for use by utilizing a small water flow rate. This research is a previous development by changing the slope of the blade angle on the turbine. The results showed the high and low values ​​of the contra rotating turbine rotation due to the influence of the tilt of the blade angle affect how efficiently the turbine captures power from the water flow. At the lowest blade angle, which is 15O degrees, the highest rotational speed is 240.3 rpm. The greatest power is also obtained by a turbine with a blade angle of 15O with a value of 0.5176 watts, and from the calculation of the performance efficiency of a contra rotating turbine with a blade angle of 15O, the highest value is 0.598%, so it can be concluded that the blade angle affects the performance of the contra rotating small hydro turbine.